Monitoring The Effort Curve In Physical Education For Normal And Overweight Students Using Smartwatches And Mobile Applications - Pârvu Carmen; Mocanu George Dănuț; Harabagiu Neculai; Ungurean Bogdan Constantin; Szabo Dan Alexandru (Indonesian Journal of Physical Education and Sport Science)
Study purpose. In physical education and sports lessons, correctly dosing effort is essential for optimising physical performance and adapting effort parameters, including breaks, in line with physiological principles. The study hypothesises that using smart-watches and mobile apps to monitor effort in middle school physical education lessons will reveal significant differences in effort and heart rate between overweight and average BMI students. Modern technology is expected to enhance understanding of students' physical exertion, facilitating adjustments to programs based on health status and fitness level.